The Relationship of Childbirth Self-Efficacy with Attitudes toward Vaginal Delivery in Nulliparous Women - Baanei Heravan, Mahsima (Advances in Nursing & Midwifery, 2023)
Introduction: Childbirth is a multidimensional process with physical, social, and psychological dimensions. Considering the increase in the cesarean rate in the country, the present study was conducted to determine the relationship of childbirth self-efficacy with attitudes toward vaginal delivery in nulliparous women. Methods: This study is a descriptive-correlational study that is done over 323 nulliparous pregnant women attending the health centers in the city of Zahedan in 2021–2022. Sampling was done by multi-stage method (stratified, clustered and convenient). Data were collected by participants’ demographic checklist, questionnaires of childbirth self‑efficacy questionnaire of Lowe, and attitude towards childbirth questionnaire of Harmen. The data were analyzed using Spearman’s correlation coefficient test, linear regression model, and multiple regression in SPSS software version 22. P < 0.05 was considered statistically significant. Results: The results of the Spearman test showed that there is a significant inverse linear relationship between childbirth self-efficacy and attitude toward childbirth (P=0.015), and between attitude toward childbirth and expected self-efficacy (p=0.010) and expected outcome (P=0.03). Also, based on the general linear regression model, attitude towards childbirth is predicted childbirth self-efficacy (P=0.018). Conclusions: The use of appropriate strategies should be considered to increase the belief of pregnant mothers towards the ability to perform vaginal delivery and to increase the positive attitude towards vaginal delivery in prenatal education, which can be an effective step in improving the health of mother and newborn, reducing cases of elective cesarean section, and finally the health of the society.